A fiber-like wool-based flexible zinc battery and its preparation method and application
By using rare earth oxide-doped binary metal compound active layer and conductive metal plating layer in fibrous zinc batteries, combined with cyano-containing polymer fibers, the difficulties in fibrous zinc batteries in packaging, high internal resistance and poor resistance are solved, and efficient and stable zinc battery performance is achieved, which is suitable for the energy supply of wearable electronic devices.
Patent Information
- Application Number
- CN202211141798.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-20
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2042-09-20
AI Technical Summary
Fibrous zinc batteries have difficulties in packaging, high internal resistance, poor resistance, etc., and lithium-ion batteries have limitations in energy density, safety and environmental impact, making it difficult to meet the needs of wearable electronic devices.
A rare earth oxide-doped binary metal compound active layer and conductive metal plating layer are used to combine the cyano-containing polymer fibers, and wool-based fibers are prepared through surface activation treatment and metal layer deposition technology, and combined with zinc wire negative electrode material and quasi-solid hydrogel electrolyte to construct a fibrous wool-based zinc battery.
The high conductivity, stability and energy storage characteristics of fibrous zinc batteries are achieved, the flexibility and durability of the battery are improved, and the specific capacity of 2.42-2.79mAh cm-3 can be provided at a current density of 0.25mA cm-1, and the capacity retention rate exceeds 95% after cyclic charging and discharging of 6,000 times at a current density of 1.0mA cm-1.
Smart Images

Figure CN115458720B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of fiber-shaped flexible batteries, and in particular relates to a fiber-shaped wool-based flexible zinc battery and a preparation method and application thereof. Background Art
[0002] With the continuous expansion of the wearable electronic product market, flexible and wearable energy storage devices have attracted more and more attention. Among them, fiber-shaped batteries have excellent softness, ductility, portability and deformation adaptability due to their unique one-dimensional structure, which is very suitable for combination with the traditional textile industry and application in the field of wearable electronic energy supply. In recent years, in the research frontier of fiber-shaped batteries, in addition to achieving higher electrochemical performance, the development of multifunctional, scalable and integrated systems is also an important research topic (Nature 597 (2021) 57–63; Nature Nanotech.17 (2022) 372–377). However, there are still many difficulties in the development of fiber-shaped batteries, including packaging difficulties, high battery internal resistance, poor tolerance and other problems. For decades, the chemistry and structure of lithium-ion batteries have been optimized to achieve higher energy density and better safety performance. However, in the current design system, limited lithium reserves, environmental issues, cost issues and safety issues have restricted the further development of lithium-ion batteries. Rechargeable zinc-based batteries have abundant zinc metal reserves and high theoretical capacity (820 mAh g -1 ), suitable electrochemical potential (-0.763V compared with the standard hydrogen electrode), high safety, equilibrium kinetics and good reversibility in aqueous solution have attracted widespread attention in recent years (Nature Mater. 17 (2018) 543-549). These characteristics make rechargeable zinc batteries the most competitive candidate for flexible and wearable device energy supply devices (Adv. Energy Mater. 9 (2019): 1802605). How to construct a suitable flexible conductive substrate and active materials with considerable mechanical and electrochemical stability to realize fiber-based zinc batteries suitable for wide integration in smart electronic devices or clothing requires further optimization of production technology and design strategies. Summary of the invention
[0003] In order to overcome the problems existing in the manufacturing technology and design strategy of the above-mentioned fiber-shaped rechargeable zinc battery, the purpose of the present invention is to provide a fiber-shaped wool-based flexible zinc battery and its preparation method and application.
[0004] The purpose of the present invention is achieved through the following solutions:
[0005] A wool-based fibrous flexible positive electrode material, comprising a rare earth oxide-doped binary metal compound active layer, a conductive metal coating, and a polymer fiber containing a cyano structure;
[0006] The rare earth oxide doped binary metal compound active layer is cerium dioxide doped nickel cobalt phosphorus, cerium dioxide doped nickel cobalt boron, cerium dioxide doped nickel iron phosphorus, cerium dioxide doped nickel iron boron, cerium dioxide doped cobalt iron phosphorus, cerium dioxide doped cobalt iron boron, cerium dioxide doped nickel copper phosphorus, cerium dioxide doped nickel copper boron, cerium dioxide doped cobalt copper phosphorus, cerium dioxide doped cobalt copper boron, cerium dioxide doped nickel manganese phosphorus, cerium dioxide doped nickel manganese boron, cerium dioxide doped cobalt manganese phosphorus, cerium dioxide doped cobalt manganese boron, cerium dioxide doped nickel zinc phosphorus, cerium dioxide doped nickel zinc boron, cerium dioxide doped cobalt zinc phosphorus, cerium dioxide doped nickel copper boron, cerium dioxide doped nickel copper phosphorus, cerium dioxide doped nickel manganese boron, cerium dioxide doped nickel manganese phosphorus, cerium dioxide doped nickel manganese boron, cerium dioxide doped nickel zinc phosphorus, cerium dioxide doped nickel zinc boron, cerium dioxide doped cobalt zinc phosphorus, cerium dioxide doped nickel copper phosphorus, cerium dioxide doped nickel copper boron, cerium dioxide doped nickel copper phosphorus, cerium dioxide doped nickel manganese boron, cerium dioxide doped nickel manganese phosphorus, cerium dioxide doped nickel manganese boron, cerium dioxide doped nickel manganese phosphorus, cerium dioxide doped nickel manganese boron, cerium dioxide doped nickel zinc phosphorus, cerium dioxide doped nickel copper ... One of cerium doped cobalt zinc boron, lanthanum dioxide doped nickel cobalt phosphorus, lanthanum dioxide doped nickel cobalt boron, lanthanum dioxide doped nickel iron phosphorus, lanthanum dioxide doped nickel iron boron, lanthanum dioxide doped cobalt iron phosphorus, lanthanum dioxide doped cobalt iron boron, lanthanum dioxide doped nickel copper phosphorus, lanthanum dioxide doped nickel copper boron, lanthanum dioxide doped cobalt copper phosphorus, lanthanum dioxide doped cobalt copper boron, lanthanum dioxide doped nickel manganese phosphorus, lanthanum dioxide doped nickel manganese boron, lanthanum dioxide doped cobalt manganese phosphorus, lanthanum dioxide doped cobalt manganese boron, lanthanum dioxide doped nickel zinc phosphorus, lanthanum dioxide doped nickel zinc boron, lanthanum dioxide doped cobalt zinc phosphorus or lanthanum dioxide doped cobalt zinc boron. The rare earth metal oxide doped binary metal compound active layer is a composite material with high conductivity, stability, microstructure uniformity and excellent energy storage characteristics.
[0007] The conductive metal plating layer is at least one of nickel, copper and cobalt.
[0008] The polymer fiber containing a cyano structure is at least one of acrylic fiber or synthetic fiber containing acrylic fiber.
[0009] A method for preparing a wool-based fibrous flexible positive electrode material comprises the following steps:
[0010] The polymer fiber containing cyanide structure is immersed in activation solution for surface activation treatment, and then a metal layer is deposited to obtain a conductive metal coating; the metal coating is modified with a binary metal compound doped with rare earth metal oxide to obtain a wool-based fibrous flexible positive electrode material.
[0011] The activation solution is a solution containing palladium ions or tin ions, preferably (NH4)2PdCl4 or tin chloride. More preferably, the concentration of the (NH4)2PdCl4 solution is 2-10 mM.
[0012] The plating solution used for the metal layer deposition is a mixture of a nickel source, a chelating agent, lactic acid and dimethyl ammonium borohydride (DMAB). Preferably, the mass ratio of the nickel source, the chelating agent, lactic acid and dimethyl ammonium borohydride is 40:5 to 25:5 to 15:1.
[0013] The nickel source is at least one of nickel sulfate, nickel acetate, nickel nitrate, nickel chloride and nickel acetylacetonate; the chelating agent is at least one of sodium citrate, potassium citrate, citric acid, ethylenediaminetetraacetic acid, sodium sulfite and sodium pyrophosphate.
[0014] The metal layer is deposited for 0.5-2.0 hours at a temperature of 30-60°C.
[0015] The rare earth metal oxide is at least one of cerium dioxide, lanthanum dioxide and the like.
[0016] The binary metal compound is a phosphide or boride composed of at least one binary metal combination of nickel-cobalt, nickel-copper, cobalt-copper, nickel-iron, cobalt-iron, nickel-manganese, cobalt-manganese, nickel-zinc, and cobalt-zinc.
[0017] The rare earth metal oxide doped binary metal compound modification is specifically to place the metal coating in a plating solution for deposition; the plating solution is a mixture of rare earth metal oxide, metal compound, sodium hypophosphite, sodium citrate and boric acid; preferably, the mass ratio of the rare earth metal oxide, metal compound, sodium hypophosphite, sodium citrate and boric acid is 1:30:30:20:100:30.
[0018] In the modification of binary metal compounds doped with rare earth metal oxides, the deposition temperature is 60-100° C. and the deposition time is 0.5-2.0 hours.
[0019] The rare earth metal oxide doped binary metal compound has a unit length loading of 5-10 mg cm -1 .
[0020] Application of the wool-based fibrous flexible positive electrode material in preparing batteries.
[0021] A fibrous wool-based zinc battery comprises a wool-based fibrous flexible positive electrode material, a zinc wire negative electrode material and a quasi-solid hydrogel electrolyte.
[0022] The wool-based fibrous flexible positive electrode material is as described above;
[0023] The zinc wire negative electrode material is a fibrous zinc wire; the diameter is preferably 10 to 50 μm.
[0024] The preparation method of the quasi-solid hydrogel electrolyte is specifically to dissolve a water-soluble polymer in water and then add alkali to finally form a viscous flowing colloidal quasi-solid gel electrolyte.
[0025] Preferably, the water-soluble polymer is at least one of polyvinyl alcohol, polyacrylamide and polyacrylic acid.
[0026] A method for preparing a fiber-shaped wool-based battery comprises the following steps:
[0027] The acrylic fiber positive electrode material is soaked in a quasi-solid hydrogel electrolyte, dried, and covered; then the zinc wire negative electrode material is evenly wrapped around it, and then soaked and dried in a quasi-solid hydrogel electrolyte again, so that the quasi-solid hydrogel electrolyte can effectively protect the entire device. Finally, the dried device is packaged in a heat shrink tube, and the conductive electrodes at the two poles are led out to obtain a fibrous wool-based battery.
[0028] The mechanism of the present invention is as follows: acrylic fiber itself has abundant cyanide groups, can effectively adsorb catalytic active ions and efficiently and conveniently obtain deposited active coatings through chemical plating; the binary metal compound at the positive electrode can undergo a reversible chemical reaction with the hydroxyl binary metal compound under the action of a strong base, and the metal zinc at the negative electrode undergoes a reversible redox reaction in a strong alkaline electrolyte, forming an effective potential difference between the two, thereby effectively constructing a zinc battery with a suitable potential window.
[0029] The fiber-shaped flexible zinc battery has an operating current of 0.25 mA cm -1 At a current density of 2.42-2.79 mAh cm -3 , at 1.0 mA cm -1 After 6000 cycles of charge and discharge at the same current density, the capacity retention rate exceeds 95%. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 Schematic diagram of the structure of wool-based fiber-shaped flexible zinc-based battery.
[0031] Figure 2 This is a scanning electron microscope image of the wool-based fibrous flexible positive electrode material of Example 1.
[0032] Figure 3 The yarn-based fibrous flexible positive electrode material constructed by the rare earth oxide-doped binary metal compound active layer of Example 1 was subjected to a three-electrode system at 0.5 mA cm -1 Performance curve of discharge at current density.
[0033] Figure 4 This is the performance curve of the wool-based fiber-shaped flexible zinc-based battery in Example 1 at different current density rates.
[0034] Figure 5 The yarn-based fiber-shaped flexible zinc-based battery of Example 1 is 1.0 mA cm -1 Cyclic test curve under current density.
[0035] Figure 6 The yarn-based fiber-shaped flexible zinc-based battery of Example 1 is 0.25 mA cm in the straight state and the bent state. -1Comparative discharge curves at current density.
[0036] Figure 7 This is a scanning electron microscope image of the wool-based fibrous flexible positive electrode material with a chemically deposited conductive nickel layer in the comparative example.
[0037] Figure 8 The yarn-based fibrous flexible positive electrode material with an unmodified rare earth oxide-doped binary metal compound active layer in the comparative example was subjected to a three-electrode system at 0.5 mA cm -1 Performance curve of discharge at current density.
[0038] Fig. 9 This is a scanning electron microscope image of the wool-based fibrous flexible positive electrode material constructed with a binary metal compound active layer not doped with rare earth oxide in the comparative example.
[0039] Fig.10 The yarn-based fibrous flexible positive electrode material constructed by the binary metal compound active layer without rare earth oxide doping in the comparative example has a conductivity of 0.5 mA cm under the three-electrode system. -1 Performance curve of discharge at current density.
[0040] Fig.11 The performance curves of the yarn-based fibrous flexible zinc-based battery constructed with a binary metal compound active layer doped with undoped rare earth oxide in the comparative example at different current density rates.
[0041] Fig.12 Performance curves of the yarn-based fibrous flexible zinc-based battery constructed with a rare earth oxide-doped binary metal compound active layer in Example 2 at different current density rates.
[0042] Fig.13 Performance curves of the yarn-based fibrous flexible zinc-based battery constructed with a rare earth oxide-doped binary metal compound active layer in Example 3 at different current density rates.
[0043] Fig.14 Performance curves of the yarn-based fibrous flexible zinc-based battery constructed with a rare earth oxide-doped binary metal compound active layer in Example 4 at different current density rates. DETAILED DESCRIPTION
[0044] The present invention is further described in detail below in conjunction with examples and drawings, but the embodiments of the present invention are not limited thereto.
[0045] The fiber-shaped flexible zinc-based battery based on artificial wool acrylic has a structure like Figure 1 As shown, it includes rare earth oxide doped binary metal compound modified acrylic fiber 1, commercial zinc wire 2, quasi-solid electrolyte 3, and packaging film 4
[0046] The rare earth oxide-doped binary metal compound-modified acrylic fiber 1 is the positive electrode;
[0047] The commercial zinc wire 2 is the negative electrode;
[0048] The quasi-solid electrolyte 3 is a polymer hydrogel and is located between the positive electrode and the negative electrode.
[0049] The packaging film 4 is a heat shrink packaging tube, which is used to protect the entire device.
[0050] Furthermore, the rare earth oxide doped binary metal compound modified acrylic fiber 1 comprises a rare earth oxide doped alloy compound coating, a conductive metal coating, and acrylic fiber;
[0051] Further, the rare earth oxide doped alloy compound coating is a composite material with high conductivity, stability and energy storage characteristics, specifically cerium dioxide doped nickel cobalt phosphorus, cerium dioxide doped nickel cobalt boron, cerium dioxide doped nickel iron phosphorus, cerium dioxide doped nickel iron boron, cerium dioxide doped cobalt iron phosphorus, cerium dioxide doped cobalt iron boron, cerium dioxide doped nickel copper phosphorus, cerium dioxide doped nickel copper boron, cerium dioxide doped cobalt copper phosphorus, cerium dioxide doped cobalt copper boron, cerium dioxide doped nickel manganese phosphorus, cerium dioxide doped nickel manganese boron, cerium dioxide doped cobalt manganese phosphorus, cerium dioxide doped cobalt manganese boron, cerium dioxide doped nickel zinc phosphorus, cerium dioxide doped nickel zinc boron, One of cerium dioxide doped cobalt zinc phosphorus, cerium dioxide doped cobalt zinc boron, lanthanum dioxide doped nickel cobalt phosphorus, lanthanum dioxide doped nickel cobalt boron, lanthanum dioxide doped nickel iron phosphorus, lanthanum dioxide doped nickel iron boron, lanthanum dioxide doped cobalt iron phosphorus, lanthanum dioxide doped cobalt iron boron, lanthanum dioxide doped nickel copper phosphorus, lanthanum dioxide doped nickel copper boron, lanthanum dioxide doped cobalt copper phosphorus, lanthanum dioxide doped cobalt copper boron, lanthanum dioxide doped nickel manganese phosphorus, lanthanum dioxide doped nickel manganese boron, lanthanum dioxide doped cobalt manganese phosphorus, lanthanum dioxide doped cobalt manganese boron, lanthanum dioxide doped nickel zinc phosphorus, lanthanum dioxide doped nickel zinc boron, lanthanum dioxide doped cobalt zinc phosphorus or lanthanum dioxide doped cobalt zinc boron;
[0052] Furthermore, the quasi-solid electrolyte 3 is a strong alkali-containing salt water gel with a polymer as a skeleton structure, and the polymer material is specifically one of polyvinyl alcohol, polyacrylamide, and polyacrylic acid.
[0053] Example 1
[0054] Detailed preparation process of wool-based fibrous cathode material:
[0055] (1) First, the acrylic fiber with a cleaned surface was immersed in 5 mM (NH4)2PdCl4 for 30 min. After washing away the residual (NH4)2PdCl4 solution on the surface, it was placed in a chemical nickel plating solution (nickel sulfate, sodium citrate, lactic acid and DMAB in a ratio of 40:20:10:1) at 40 degrees for 0.5 hours to obtain an acrylic conductive fiber wrapped with a metal nickel layer.
[0056] (2) After cleaning the residual plating solution, the nickel-plated acrylic fiber was further immersed in a composite plating solution of binary nickel cobalt phosphide doped with cerium dioxide (cerium dioxide, nickel chloride, cobalt chloride, sodium hypophosphite, sodium citrate and boric acid in a ratio of 1:30:30:20:100:30), stirred continuously at 20 rpm, and reacted at 90°C for 1 hour to obtain a wool-based fibrous flexible positive electrode material with a microscopic morphology as shown in FIG. Figure 2 Scanning electron microscopy.
[0057] Quasi-solid polymer hydrogel preparation process:
[0058] Subsequently, polyvinyl alcohol (PVA) was added to water (PVA: water = 1:10), and stirring was continued at 85°C for 1 hour. Potassium hydroxide powder was then added and stirred to dissolve (PVA: potassium hydroxide = 5:1) for another 4 hours to finally obtain a viscous quasi-solid hydrogel electrolyte.
[0059] Preparation process of fiber-like yarn-based zinc battery:
[0060] The acrylic fiber positive electrode material is soaked in a quasi-solid hydrogel electrolyte, dried, and covered; then the zinc wire negative electrode material is evenly wrapped around it, and then soaked and dried in a quasi-solid hydrogel electrolyte again, so that the quasi-solid hydrogel electrolyte can effectively protect the entire device. Finally, the dried device is packaged in a heat shrink tube, and the conductive electrodes at the two poles are led out to obtain a fibrous wool-based battery.
[0061] The prepared fibrous flexible cathode material has a high conductivity at 0.50 mA cm -1 The current density is 14.5 μAh cm -2 The specific capacity (such as Figure 3 As shown. The three-electrode system, counter electrode: carbon rod, reference electrode: Ag / AgCl electrode), combined with commercial zinc wire (diameter 20 μm) to form a fiber-shaped flexible zinc battery at 0.25 mA cm -1 The current density is 2.51 mAh cm -3 Specific capacity (such as Figure 4 shown), at 1.0 mA cm -1 The capacity can be maintained at 95% after 6000 cycles at a current density of Figure 5When the device is bent 90 degrees, the capacity can be maintained at 96% of the original value (as shown in Figure 6 shown).
[0062] Example 2
[0063] Detailed preparation process of wool-based fibrous cathode material:
[0064] (1) First, the acrylic fiber with a cleaned surface was immersed in 5 mM (NH4)2PdCl4 for 30 min. After washing away the residual (NH4)2PdCl4 solution on the surface, it was placed in a chemical nickel plating solution (nickel sulfate, sodium citrate, lactic acid and DMAB in a ratio of 40:20:10:1) at 40 degrees for 0.5 hours to obtain an acrylic conductive fiber wrapped with a metal nickel layer.
[0065] (2) After cleaning the residual plating solution, the nickel-plated acrylic fiber is further immersed in a composite plating solution of binary nickel-iron phosphide doped with lanthanum dioxide (lanthanum dioxide, nickel chloride, ferric chloride, sodium hypophosphite, sodium citrate and boric acid in a ratio of 1:30:20:20:100:30), continuously stirred at a speed of 20 rpm, and reacted at 85°C for 0.5 hour to obtain a wool-based fibrous flexible positive electrode material.
[0066] Preparation process of fiber-like yarn-based zinc battery:
[0067] The acrylic fiber positive electrode material is soaked in a quasi-solid hydrogel electrolyte, dried, and covered; then the zinc wire negative electrode material is evenly wrapped around it, and then soaked and dried in a quasi-solid hydrogel electrolyte again, so that the quasi-solid hydrogel electrolyte can effectively protect the entire device. Finally, the dried device is packaged in a heat shrink tube, and the conductive electrodes at the two poles are led out to obtain a fibrous wool-based battery.
[0068] The fiber-shaped flexible zinc battery has an operating current of 0.25 mA cm -1 The current density is 2.42 mAh cm -3 Specific capacity (such as Fig.12 shown).
[0069] Example 3
[0070] Detailed preparation process of wool-based fibrous cathode material:
[0071] (1) First, the acrylic fiber with a cleaned surface was immersed in 5 mM (NH4)2PdCl4 for 30 min. After washing away the residual (NH4)2PdCl4 solution on the surface, it was placed in a chemical nickel plating solution (nickel sulfate, sodium citrate, lactic acid and DMAB in a ratio of 40:20:10:1) at 40 degrees for 0.5 hours to obtain an acrylic conductive fiber wrapped with a metal nickel layer.
[0072] (2) After cleaning the residual plating solution, the nickel-plated acrylic fiber is further immersed in a composite plating solution of binary nickel cobalt boride doped with cerium dioxide (cerium dioxide, nickel chloride, cobalt chloride, DMAB, sodium citrate and boric acid in a ratio of 1:30:30:20:100:30) and continuously stirred at a speed of 20 rpm, and reacted at 90°C for 1 hour to obtain a wool-based fibrous flexible positive electrode material.
[0073] Preparation process of fiber-like yarn-based zinc battery:
[0074] The acrylic fiber positive electrode material is soaked in a quasi-solid hydrogel electrolyte, dried, and covered; then the zinc wire negative electrode material is evenly wrapped around it, and then soaked and dried in a quasi-solid hydrogel electrolyte again, so that the quasi-solid hydrogel electrolyte can effectively protect the entire device. Finally, the dried device is packaged in a heat shrink tube, and the conductive electrodes at the two poles are led out to obtain a fibrous wool-based battery.
[0075] The fiber-shaped flexible zinc battery has an operating current of 0.25 mA cm -1 The current density is 2.79 mAh cm -3 Specific capacity (such as Fig.13 shown).
[0076] Example 4
[0077] Detailed preparation process of wool-based fibrous cathode material:
[0078] (1) First, the acrylic fiber with a cleaned surface was immersed in 5 mM (NH4)2PdCl4 for 30 min. After washing away the residual (NH4)2PdCl4 solution on the surface, it was placed in a chemical nickel plating solution (nickel sulfate, sodium citrate, lactic acid and DMAB in a ratio of 40:20:10:1) at 40 degrees for 0.5 hours to obtain an acrylic conductive fiber wrapped with a metal nickel layer.
[0079] (2) After cleaning the residual plating solution, the nickel-plated acrylic fiber is further immersed in a composite plating solution of binary cobalt iron phosphide doped with lanthanum dioxide (lanthanum dioxide, cobalt chloride, ferric chloride, DMAB, sodium citrate and boric acid in a ratio of 1:30:20:20:100:30), continuously stirred at a speed of 20 rpm, and reacted at 85°C for 1 hour to obtain a wool-based fibrous flexible positive electrode material.
[0080] Preparation process of fiber-like yarn-based zinc battery:
[0081] The acrylic fiber positive electrode material is soaked in a quasi-solid hydrogel electrolyte, dried, and covered; then the zinc wire negative electrode material is evenly wrapped around it, and then soaked and dried in a quasi-solid hydrogel electrolyte again, so that the quasi-solid hydrogel electrolyte can effectively protect the entire device. Finally, the dried device is packaged in a heat shrink tube, and the conductive electrodes at the two poles are led out to obtain a fibrous wool-based battery.
[0082] The fiber-shaped flexible zinc battery has an operating current of 0.25 mA cm -1 The current density is 2.65 mAh cm -3 Specific capacity (such as Fig.14 shown).
[0083] Comparative Example
[0084] Detailed preparation process of wool-based fibrous cathode material:
[0085] (1) First, the acrylic fiber with a clean surface was immersed in 5 mM (NH4)2PdCl4 for 30 min. After washing the residual (NH4)2PdCl4 solution on the surface, it was placed in a chemical nickel plating solution (nickel sulfate, sodium citrate, lactic acid and DMAB in a ratio of 40:20:10:1) at 40 degrees for 0.5 hours to obtain a metal nickel layer-wrapped acrylic conductive fiber. The microscopic morphology is shown in FIG. Figure 7 Scanning electron microscopy. The electrode was -1 The current density is 0.536 μAh cm -2 The specific capacity (such as Figure 8 shown).
[0086] (2) After cleaning the residual plating solution, the nickel-plated acrylic fiber was further immersed in a binary nickel-cobalt phosphide plating solution (nickel chloride, cobalt chloride, sodium hypophosphite, sodium citrate and boric acid in a ratio of 30:30:20:100:30) and stirred at 20 rpm, and reacted at 90 ° C for 1 hour to obtain a wool-based fibrous flexible positive electrode material. The microscopic morphology is shown in FIG. Fig. 9 Scanning electron microscopy.
[0087] Quasi-solid polymer hydrogel preparation process:
[0088] Subsequently, polyvinyl alcohol (PVA) was added to water (PVA: water = 1:10), and stirring was continued at 85°C for 1 hour. Potassium hydroxide powder was then added and stirred to dissolve (PVA: potassium hydroxide = 5:1) for another 4 hours to finally obtain a viscous quasi-solid hydrogel electrolyte.
[0089] Preparation process of fiber-like yarn-based zinc battery:
[0090] The wool-based fibrous flexible positive electrode material is soaked in a quasi-solid hydrogel electrolyte, dried, and covered; then the zinc wire negative electrode material is evenly wrapped around it, and then soaked and dried in a quasi-solid hydrogel electrolyte again, so that the quasi-solid hydrogel electrolyte can effectively protect the entire device. Finally, the dried device is packaged in a heat shrink tube, and the conductive electrodes at the two poles are led out to obtain a fibrous wool-based battery.
[0091] The prepared fibrous flexible cathode material has a high conductivity at 0.50 mA cm -1 The current density is 3.46 μAh cm -2 The specific capacity (such as Fig.10 The fiber-shaped flexible zinc battery composed of it and commercial zinc wire (20 μm in diameter) was tested at 0.25 mA cm -1 The current density is 0.832 mAh cm -3 Specific capacity (such as Fig.11 shown).
Claims
1. A wool-based fibrous flexible positive electrode material, characterized in that It includes a rare earth oxide doped binary metal compound active layer, a conductive metal coating, and acrylic fiber; The rare earth oxide doped binary metal compound active layer is cerium dioxide doped nickel cobalt phosphorus, cerium dioxide doped nickel cobalt boron, cerium dioxide doped nickel iron phosphorus, cerium dioxide doped nickel iron boron, cerium dioxide doped cobalt iron phosphorus, cerium dioxide doped cobalt iron boron, cerium dioxide doped nickel copper phosphorus, cerium dioxide doped nickel copper boron, cerium dioxide doped cobalt copper phosphorus, cerium dioxide doped cobalt copper boron, cerium dioxide doped nickel manganese phosphorus, cerium dioxide doped nickel manganese boron, cerium dioxide doped cobalt manganese phosphorus, cerium dioxide doped cobalt manganese boron, cerium dioxide doped nickel zinc phosphorus, cerium dioxide doped nickel zinc boron, cerium dioxide doped cobalt zinc phosphorus, cerium dioxide doped nickel copper boron, cerium dioxide doped nickel copper phosphorus, cerium dioxide doped nickel manganese boron, cerium dioxide doped nickel manganese phosphorus, cerium dioxide doped nickel manganese boron, cerium dioxide doped nickel zinc phosphorus, cerium dioxide doped nickel zinc boron, cerium dioxide doped cobalt zinc phosphorus, cerium dioxide doped nickel copper phosphorus, cerium dioxide doped nickel copper boron, cerium dioxide doped nickel copper phosphorus, cerium dioxide doped nickel manganese boron, cerium dioxide doped nickel manganese phosphorus, cerium dioxide doped nickel manganese boron, cerium dioxide doped nickel manganese phosphorus, cerium dioxide doped nickel manganese boron, cerium dioxide doped nickel zinc phosphorus, cerium dioxide doped nickel copper ... One of cerium doped cobalt zinc boron, lanthanum dioxide doped nickel cobalt phosphorus, lanthanum dioxide doped nickel cobalt boron, lanthanum dioxide doped nickel iron phosphorus, lanthanum dioxide doped nickel iron boron, lanthanum dioxide doped cobalt iron phosphorus, lanthanum dioxide doped cobalt iron boron, lanthanum dioxide doped nickel copper phosphorus, lanthanum dioxide doped nickel copper boron, lanthanum dioxide doped cobalt copper phosphorus, lanthanum dioxide doped cobalt copper boron, lanthanum dioxide doped nickel manganese phosphorus, lanthanum dioxide doped nickel manganese boron, lanthanum dioxide doped cobalt manganese phosphorus, lanthanum dioxide doped cobalt manganese boron, lanthanum dioxide doped nickel zinc phosphorus, lanthanum dioxide doped nickel zinc boron, lanthanum dioxide doped cobalt zinc phosphorus or lanthanum dioxide doped cobalt zinc boron; The conductive metal plating layer is at least one of nickel, copper and cobalt; The acrylic fiber is at least one of acrylic fiber or synthetic fiber containing acrylic fiber; The method for preparing the wool-based fibrous flexible positive electrode material comprises the following steps: The acrylic fiber is immersed in an activation solution for surface activation treatment, and then a metal layer is deposited to obtain a conductive metal coating; the conductive metal coating is modified with a binary metal compound doped with a rare earth oxide to obtain a wool-based fibrous flexible positive electrode material.
2. A method for preparing the wool-based fibrous flexible positive electrode material according to claim 1, characterized in that The following steps are involved: The acrylic fiber is immersed in an activation solution for surface activation treatment, and then a metal layer is deposited to obtain a conductive metal coating; the conductive metal coating is modified with a binary metal compound doped with a rare earth oxide to obtain a wool-based fibrous flexible positive electrode material.
3. The method according to claim 2, characterized in that: The activation solution is a solution containing palladium ions or tin ions.
4. The method according to claim 2, characterized in that: The plating solution used for the metal layer deposition is a mixture of a nickel source, a chelating agent, lactic acid and dimethyl ammonium borohydride; The mass ratio of nickel source, chelating agent, lactic acid and dimethyl ammonium borohydride is 40:5~25:5~15:1; The nickel source is at least one of nickel sulfate, nickel acetate, nickel nitrate, nickel chloride and nickel acetylacetonate; the chelating agent is at least one of sodium citrate, potassium citrate, citric acid, ethylenediaminetetraacetic acid, sodium sulfite and sodium pyrophosphate.
5. The method according to claim 2, characterized in that: The rare earth oxide doped binary metal compound modification is specifically to place the metal coating in a plating solution for deposition; the plating solution is a mixture of rare earth metal oxide, metal compound, sodium hypophosphite, sodium citrate and boric acid.
6. The method according to claim 5, characterized in that: The metal layer is deposited for 0.5-2.0 hours at a temperature of 30-60° C.; in the modification of binary metal compounds doped with rare earth oxides, the deposition temperature is 60-100° C. and the deposition time is 0.5-2.0 hours.
7. A fiber-like yarn-based zinc battery, characterized in that It comprises the wool-based fibrous flexible positive electrode material as described in claim 1, a zinc wire negative electrode material and a quasi-solid hydrogel electrolyte.
8. The fiber-like yarn-based zinc battery according to claim 7, characterized in that: The zinc wire negative electrode material is a fibrous zinc wire; The preparation method of the quasi-solid hydrogel electrolyte is specifically to dissolve a water-soluble polymer in water and then add alkali to finally form a viscous flowing colloidal quasi-solid gel electrolyte.
9. A method for preparing the fibrous yarn-based zinc battery according to claim 7 or 8, characterized in that The following steps are involved: The wool-based fiber-shaped flexible positive electrode material is immersed in a quasi-solid hydrogel electrolyte, dried, and covered and wrapped; Subsequently, the zinc wire negative electrode material is evenly wrapped around it, and then immersed and dried again in a quasi-solid hydrogel electrolyte, so that the quasi-solid hydrogel electrolyte can effectively protect the entire device. Finally, the dried device is packaged in a heat shrink tube, and the conductive electrodes at the two poles are led out to obtain a fibrous wool-based battery.
Citation Information
Patent Citations
Preparation method of flexible cloth electrode based on nickel manganese hydroxide
CN109267047A
Flexible zinc ion hybrid capacitor and preparation method and application thereof
CN112216518A